2009
DOI: 10.1128/aem.00639-09
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of Salmonella enterica Serovar Enteritidis Fimbrial Protein SefA as a Surface Protein in Escherichia coli Confers the Ability To Attach to Eukaryotic Cell Lines

Abstract: The gene for the Salmonella enterica serovar Enteritidis fimbrial protein SefA was cloned into an Escherichia coli surface expression vector and confirmed by Western blot assay. E. coli clones expressing SefA attached to avian ovary granulosa cells and HEp-2 cells, providing evidence for the involvement of SefA in the ability of Salmonella to attach to eukaryotic cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…7b). Adhesion phenotype mediated by fimbrial genes expressed in E. coli strains was observed for other Salmonella fimbriae, such as Stg and Sef (Forest et al, 2007;Rank et al, 2009), confirming that fimbriae can contribute to the interaction with host cells.…”
Section: Discussionmentioning
confidence: 74%
“…7b). Adhesion phenotype mediated by fimbrial genes expressed in E. coli strains was observed for other Salmonella fimbriae, such as Stg and Sef (Forest et al, 2007;Rank et al, 2009), confirming that fimbriae can contribute to the interaction with host cells.…”
Section: Discussionmentioning
confidence: 74%
“…It was suggested that gene loss may be a mechanism of targeting the invading pathogen preferentially to particular tissues or host cells, and can also influence the ability of the pathogen to survive in the external environment or even in stressful situations within the host (Thomson et al, 2008;Feng et al, 2013). The enhanced invasion of the reproductive tract and survival in the forming egg of S. Enteritidis and S. Gallinarum has been linked to the presence of SEF-14 fimbriae ( (Peralta et al, 1994;Thiagarajan et al, 1996;Rajashekara et al, 2000;Rank et al, 2009). S. Enteritidis can colonize the intestinal epithelium of chickens and is then able to reach a variety of internal organ sites, notably the ovaries (Gast and Beard, 1990;Gast, 1994;Peralta et al, 1994;Thiagarajan et al, 1996;Rajashekara et al, 2000;Rank et al, 2009;Berghaus et al, 2011).…”
Section: Factors Influencing Salmonella Pathogenesis In Chickensmentioning
confidence: 99%
“…The enhanced invasion of the reproductive tract and survival in the forming egg of S. Enteritidis and S. Gallinarum has been linked to the presence of SEF-14 fimbriae ( (Peralta et al, 1994;Thiagarajan et al, 1996;Rajashekara et al, 2000;Rank et al, 2009). S. Enteritidis can colonize the intestinal epithelium of chickens and is then able to reach a variety of internal organ sites, notably the ovaries (Gast and Beard, 1990;Gast, 1994;Peralta et al, 1994;Thiagarajan et al, 1996;Rajashekara et al, 2000;Rank et al, 2009;Berghaus et al, 2011). Studies have shown that some S. Enteritidis phage types (PTs) are more invasive than others (Hinton et al, 1990;Roy et al, 2001), but other similarly designed studies could not identify any difference in the invasiveness or colonisation ability between different phage types (Barrow, 1991).…”
Section: Factors Influencing Salmonella Pathogenesis In Chickensmentioning
confidence: 99%
“…S. Enteritidis also has the ability to alter the cell surface dramatically; it frequently produces glycosylated high-molecularmass LPS that may be important for persistence in eggs and may assist the efficiency of transmission of infection to man (Jean Guard-Petter, 2001). S. Enteritidis fimbrial protein (SefA) is also involved in the superior ability of S. Enteritidis to attach to ovarian granulosa cells and other cells (Rank et al, 2009). All these findings suggest that S. Enteritidis has a higher ability to colonise the reproductive epithelium than other serovars, and that the Salmonella LPS type may play an essential role in tropism of the reproductive tract.…”
Section: B Salmonella Contamination Of the Egg Contentsmentioning
confidence: 99%